Far-field emission narrowing effect of microdisk lasers - Lee, TD; Cheng, PH; Pan, JS; Tsai, RS; Lai, Y; Tai, K (My University, 1998)
Far-field intensity distribution of semiconductor microdisk lasers is experimentally measured and the emission angle is found to be much smaller than that of a planar source with the same near-held width. In fact the emission angle is determined mainly by the disk radius instead of the disk thickness. A scalar diffraction theory in the cylindrical coordinate is developed to explain such an emission-angle-narrowing phenomenon and numerical calculation based on a vectorial diffraction theory is carried out to explain the measured polarization state. (C) 1998 American Institute of Physics.